Etiological Roles of p75NTR in a Mouse Model of Wet Age-Related Macular Degeneration - Subirada Caldarone, Paula Virginia (2023)
Choroidal neovascularization (CNV) is a pathological angiogenesis of the choroidal plexus of the retina and is a key feature in the wet form of age-related macular degeneration. Mononuclear phagocytic cells (MPCs) are known to accumulate in the subretinal space, generating a chronic inflammatory state that promotes the growth of the choroidal neovasculature. However, how the MPCs are recruited and activated to promote CNV pathology is not fully understood. Using genetic and pharmacological tools in a mouse model of laser-induced CNV, we demonstrate a role for the p75 neurotrophin receptor (p75NTR) in the recruitment of MPCs, in glial activation, and in vascular alterations. After laser injury, expression of p75NTR is increased in activated Muller glial cells near the CNV area in the retina and the retinal pigmented epithelium (RPE)-choroid. In p75NTR knockout mice (p75NTR KO) with CNV, there is significantly reduced recruitment of MPCs, reduced glial activation, reduced CNV area, and the retinal function is preserved, as compared to wild type mice with CNV. Notably, a single intravitreal injection of a pharmacological p75NTR antagonist in wild type mice with CNV phenocopied the results of the p75NTR KO mice. Our results demonstrate that p75NTR is etiological in the development of CNV.